2021
DOI: 10.1159/000521393
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Representational and Behavioral Measures of Parent-Child Attachment Available for Middle Childhood

Abstract: A variety of parent-child attachment measures, representing a range of conceptual approaches, have been adapted for use in middle childhood. A recent surge in studies using the new methods makes a comprehensive review of these measures timely. This systematic review of 67 studies covers representational and behavioral measures of parent-child attachment used with children 9-12 years old. This paper aims to evaluate parent-child attachment measurements with an emphasis on understanding their theoretical base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 108 publications
(298 reference statements)
0
9
0
Order By: Relevance
“…The field of study of attachment in middle childhood owes much to Kathy Kerns (e.g., Kerns & Richardson, 2005), as this period of the human developmental lifespan was the last to be investigated from an attachment perspective, after infancy, adulthood, adolescence, and the older/oldest years of the lifespan. This paper by Gastelle and Kerns (2022) underscores how far the field has come in the last 20 years, with a large set of useful suggestions, some of which have been elaborated on in this commentary, that may profitably guide further research and meaningful clinical work.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The field of study of attachment in middle childhood owes much to Kathy Kerns (e.g., Kerns & Richardson, 2005), as this period of the human developmental lifespan was the last to be investigated from an attachment perspective, after infancy, adulthood, adolescence, and the older/oldest years of the lifespan. This paper by Gastelle and Kerns (2022) underscores how far the field has come in the last 20 years, with a large set of useful suggestions, some of which have been elaborated on in this commentary, that may profitably guide further research and meaningful clinical work.…”
Section: Discussionmentioning
confidence: 84%
“…Ainsworth et al (1978) showed that observations of maternal sensitivity in the home over the first year of life predicted infant-mother attachment behavior at 1 year of age. And much longitudinal research has shown how infant-mother, and though studied less frequently infant-father attachment, have been linked forward in time predictively to a wide range of socioemotional outcomes across childhood and into Human Development 2022;66:30-33 DOI: 10.1159/000521528 adolescence, as Gastelle and Kerns (2022) review early in their paper. Yet, in their narrative review of 67 papers studying attachment in middle childhood, and diverse measures of attachment representations, behaviors, and questionnaire responses, predictive validity is not mentioned.…”
Section: The Need For Predictive Validity Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, representational measures of attachment evaluate children's reflections on attachment relationship experiences and secure base script mental representations. Representational measures of attachment include word prompts, story stem completion tasks, and autobiographical interviews or narrative measures (Gastelle & Kerns, 2022). For instance, the Friends and Family Interview (Steele & Steele, 2005) and Child Attachment Interview (Target et al, 2003) are autobiographical interview measures for children, and the Adult Attachment Interview (Main et al, 1985) is an autobiographical interview measure for adolescents and emerging adults.…”
Section: Conceptual Relations Between Attachment and Trait Measures O...mentioning
confidence: 99%